The subjective acceptance in presbyopic patient receiving correction based on conventional method of age v/s amplitude of accommodation - Chaudhary, Neha Priyadarshani; Gautam, Pramod Sharma (Journal of Nepalgunj Medical College, 2019)
Objective: To observe the subjective acceptance in presbyopic patients following prescription of spectacles.Material and method: This is a hospital based cross sectional study which was conducted in 100 presbyopic patients in age group of 35 to 60 years at outpatient department of ophthalmology in Nobel Medical College Teaching Hospital, kanchanbari from 1 August 2018 to 30November 2018. The patients were divided into two groups, First group received the presbyopic correction according to conventional method of age and the second group received the prescription according to their amplitude of accommodation. Patient's satisfaction in terms of symptoms like eyestrain, headache or difficulty with the usage of glasses was noted. The data collected were subjected to statistical analysis.Conclusion: When presbyopic correction is given according to amplitude of accommodation in patients belonging to 36-45 years age group, it is tolerated better and patients are more satisfied in terms of symptoms like eyestrain and headache than getting the simple correction as per their age. However after the age of 45 years, presbyopic correction given according to age is equally tolerated well among all refractive error groups.Results: 100 patients in this study who visited our OPD with presbyopic symptoms were divided into two groups, each of 50 patients. Patient's satisfaction and tolerance was better when presbyopic correction was given on the basis of their amplitude of accommodation in age group 36-45, in comparison to the prescription given according to conventional method of their age. However, there was no statistically significant difference in the patient's satisfaction level in the two groups after the age of 45.